2013
DOI: 10.1039/c3sc00056g
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis of (±)-leuconolam: intramolecular allylic silane addition to a maleimide carbonyl group

Abstract: A concise total synthesis of the plant alkaloid (±)-leuconolam (1) has been achieved. A regio- and diastereoselective Lewis-acid mediated allylative cyclization was used to establish, simultaneously, two adjacent tetrasubstituted carbon centers. Furthermore, an essential arene cross-coupling to a hindered haloalkene was enabled by the use of a novel 2-anilinostannane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…A related strategy involving carbon nucleophilic species was reported by Hoye and co-workers during their studies on the total synthesis of (±)-leuconolam. 44 Indeed, a Lewis acid mediated intramolecular allylsilane addition onto maleimides derivatives was used as the key step. Initially, various Lewis acids were screened as the activator and it was found that MeAlCl 2 facilitated Sakurai-type intramolecular 1,2-addition of allylsilane onto the symmetrical…”
Section: Scheme 22 Addition Of Organometallic Reagents Onto Maleimidementioning
confidence: 99%
“…A related strategy involving carbon nucleophilic species was reported by Hoye and co-workers during their studies on the total synthesis of (±)-leuconolam. 44 Indeed, a Lewis acid mediated intramolecular allylsilane addition onto maleimides derivatives was used as the key step. Initially, various Lewis acids were screened as the activator and it was found that MeAlCl 2 facilitated Sakurai-type intramolecular 1,2-addition of allylsilane onto the symmetrical…”
Section: Scheme 22 Addition Of Organometallic Reagents Onto Maleimidementioning
confidence: 99%
“…In 2013, Hoye and co-workers reportedaconcise 14-step total synthesis of (AE)-leuconolam (10)i n7 %o verall yield. [22] The key feature was ar egio-and diastereoselective Lewis acid mediated allylative cyclization formingt he carbinolamide subunit with two adjacent tetrasubstituted carbon centers in one step (Scheme 12).…”
Section: Leuconolammentioning
confidence: 99%
“…In 2013, Hoye and co‐workers reported a concise 14‐step total synthesis of (±)‐leuconolam ( 10 ) in 7 % overall yield . The key feature was a regio‐ and diastereoselective Lewis acid mediated allylative cyclization forming the carbinolamide subunit with two adjacent tetrasubstituted carbon centers in one step (Scheme ).…”
Section: Total Synthesesmentioning
confidence: 99%
“…Leuconolam ( 10 ), first isolated by Goh from Leuconotis plants in 1984, represents a tetracyclic nine‐membered lactam originating from oxidative ring opening of the indole core, and contains an α,β‐unsaturated carbinolamide subunit (highlighted in red, Figure ). Two total syntheses, which are discussed herein (vide infra), were reported from the groups of Banwell and Hoye . The two closely related analogues, rhazinilam ( 11 ) and rhazinal ( 12 ) only differ from 10 by possessing a pyrrole core.…”
Section: Introductionmentioning
confidence: 99%